Analisis Pendapatan Dan Kelayakan Usaha Pembuatan Opak Ubi Kayu (Manihot ecaulenta) Di Desa Candi Rejo Dan Sidodadi Kecamatan Biru – Biru Kabupaten Deli Serdang - Sinaga, Handiko Pasugian; Ariani, Sri; Nurcahyani, Marizha (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
This study aims to determine the amount of income obtained by cassava opak craftsmen and to analyze the feasibility of cassava opak craftsmen's business. This study was conducted in Candi Rejo Village and Sidodadi Village, Biru - Biru District, Deli Serdang Regency in February - March 2025. Sampling in this study used a purposive sampling method with 23 respondents. The data analysis methods used were Income Analysis and Feasibility Analysis. The results of this study are that the average income obtained by cassava opak craftsmen in 1 month is IDR 5,228,325 with an average cassava opak production of 600.347 Kg and a selling price of IDR 26,000 / kg. So that the income obtained is IDR 15,609,043 with a cost of IDR 10,380,178 in 1 month. The R/C ratio value obtained by the cassava opak craftsmen was 1.50 where the R/C value in the cassava opak making business was 1, with the interpretation that the cassava opak making business in Candi Rejo Village and Sidodadi Village is feasible to be attempted in running a cassava opak making business.